Percutaneous embolization of a giant collateral vessel originating from the azygos vein via the inferior vena cava. Issue 6 (24th July 2013) - Witzke, Christian; Bhatt, Ami; Inglessis, Ignacio
<x xml:space="preserve">Abstract</x> We present the case of a 45‐year‐old man with univentricular heart, small outlet chamber, and L‐transposition of the great vessels. As an infant, the patient underwent multiple palliative surgical interventions. He presented with worsening dyspnea and fatigue and was found to have systemic oxygen saturation of 85% on 2 L of oxygen by nasal cannula, whereas he had chronically remained between 90 and 95% throughout most of adulthood. There was no evidence of significant valvular regurgitation or stenosis, nor was there an overt intracardiac shunt by echocardiography. Cardiac CT and cardiac MRI revealed a large serpiginous systemic to pulmonary venovenous collateral located behind the left atrium. The collateral drained into the lower right pulmonary vein as it entered the left atrium. The tributary veins to the "giant" collateral were determined by these images modalities. The patient underwent a percutaneous embolization of this giant venovenous collateral via a remnant supracardinal vein originating from the infrarenal inferior vena cava using two Amplatzer Vascular Plug II. Immediately after the procedure the patient's oxygen saturation increased to 90% on room air at rest. At 2 months follow‐up the patient had a marked clinical improvement with oxygen saturation as high as 95% on room air while walking. Our case illustrates a successful embolization of a giant collateral via an embryological venous remnant connecting the IVC to the azygos system. © 2012 Wiley Periodicals, Inc.